Modalità e tematiche contemporanee dell’attivismo trans* in Italia. Forme di resistenza e cura | Modes and Themes of Trans* Activism in Italy. Forms of Resistance and Care - Sterbini Perticarà, Michel (SocietàMutamentoPolitica, 2025)
Research focusing on the rights of trans* people highlight different discriminations encountered in various aspects of daily life, such as workplaces or healthcare settings. The gender binary that structures the social order impedes the recognition of self-affirmation and the protection of personal human rights. In response to institutional lacks and political attacks, the trans* community develops different resistance mechanisms, organising itself into associations, advocacy groups, and networks. This article explores queer activism in Italy, with a particular focus on the trans* movement and its collective care practices, developed both through physical and virtual spaces, as a response to these daily and systemic forms of discrimination. Using qualitative methodologies such as semi-structured individual interviews and desk analysis of online pages, this paper concentrates on the issues followed by young trans and non-binary individuals in Italy through their activism, and the various forms of direct social action they engage in. These practices claim spaces of autonomy and create networks of convergence, promoting self-affirmation while combating isolation and exclusion. The analysis therefore reveals how activism can serve as a source of individual and collective care and emancipation, where mutual aid and resource exchange act as practical laboratories for a solidarity that can drive social change.